Putting the Freeze on Priming: The Role of Need for Cognitive Closure on the Prime-Norm Dynamic. (July 2014) - Jia, Lile; Hirt, Edward R.; Evans, Douglas N.
Past research has indicated that individuals with a high need for cognitive closure (NFCC) are more susceptible to priming effects in norm-absent contexts. We proposed that in norm-present contexts, whereby normative information competes with priming in affecting individuals' understanding of the social environment, the opposite pattern would occur. In Study 1, low- rather than high-NFCC individuals showed greater prime-consistent behavior in a context with a strong norm to comply. In Study 2, when both priming and normative information were manipulated, priming dictated low-NFCC individuals' behaviors, whereas norms guided high-NFCC individuals' behavior. In Study 3, the effect of a single priming manipulation was observed in two consecutive contexts. While high-NFCC individuals, compared with low-NFCC ones, were less prime-consistent in the norm-present context, they were more influenced by the same priming manipulation in the norm-absent context. Our findings underscore the importance of NFCC in people's selection of environmental cues to guide self-regulation.